A complicated full sibling identification case solved using three statistical methods. Issue 1 (December 2019) - Ren, He; Liu, Zhiyong; Chen, Man; Zhao, Jing; Cheng, Feng; Li, Chen; Chen, Chuguang; Liu, Yacheng; Yan, Jiangwei
Highlights: A complicated full sibling identification case solved by three statistical methods. It was meaningful for forensic practice. Abstract: Full sibling (FS) identification is commonly encountered in daily practice. The established FS industry standard in China for identity-by-state (IBS), which is based on scores of shared alleles between individuals, is IBS ≥ 42 scores, when the error rate is ≤ 0.001% and 39 autosomal STRs are used. By using this standard, the vast majority of cases are successfully identified. Here, we report a FS identification case, wherein the IBS score was only 39, after typing 39 autosomal STRs. Therefore, ITO and IBS based on heterozygosity methods were utilized simultaneously. In the ITO method, FS value reached 2.21 × 10 4, which exceeded the half sibling (HS) value (1.15 × 10 3 ), and the result of IBS based on heterozygosity supported the FS conclusion (FS/HS ratio was 2.71). The genotypes from mitochondrial DNA and Y-STRs also supported the FS relationship. Thus, in practice, an exclusion conclusion should not be hurriedly drawn, even though the IBS scores are less than 42. Rather, multiple kits and statistical methods should be applied to confirm such conditions.